Estresse fisiológico e estratégias de enfrentamento : um estudo com crianças hospitalizadas - Moraes, Alessandra Ribeiro de (2021)
Child hospitalization is considered an adverse event in child development, which can cause different consequences for both the child and the family, such as the presence of indicators of anxiety, depression, stress, difficulty in relating to the health team, difficulty in regarding adaptation to hospital rules, among others. The present study investigated the physiological stress and coping strategies of 20 hospitalized children (average age: 5.75; SD = 0.85) and their family caregiver. To this end, two studies were carried out, namely: 1) Study 1 - Database - analysis of a database of a developed research that investigated psychosocial variables of child hospitalization. The following instruments were analyzed: a) Interview guide on illness and hospitalization - caregiver version; b) Salivary cortisol index; c) Hospitalization coping scale (COPE-H); 2) Study 2 - Complementary data - analysis of variables investigated using the following instruments: a) Sociodemographic data present in the interview script about illness and hospitalization - caregiver version; b) Interview guide on illness and hospitalization - child version; c) Questionnaire to identify stressful events - child version; d) Child Behavior Checklist 1½- 5 anos (CBCL) and Child Behavior Checklist 6/18 anos (CBCL). The results revealed that: 1) sociodemographic aspect of the family: mother is the main caregiver, the family income was concentrated between 1 to 3 minimum wages, complete average education level, living in their own home; most children have a chronic disease, the family caregiver perceives a change in their routine, and they report feeling fear, sadness, worry, nervousness and guilt, they expect to cure the disease and have support; 2) stress: only 4 children indicated the presence of physiological stress; 3) behavior problems: more than half of the children indicated behavior problems; 4) Coping: the most frequent behaviors during hospitalization were playing, watching TV, talking and taking medication, while the less frequent ones were running away and hiding. Coping of involuntary and voluntary disengagement was observed; 5) Stress and coping: there was no significant correlation between stress and coping. In general, there was consonance with literature in the area regarding the limitations imposed by hospitalization and the psychosocial consequences for both the child and the family caregiver. There is a need for further studies on stress in children's hospitalization in order to think about the most diverse variables involved in this context. The type of referenced coping portrays the child's need to get away from the stressor involuntarily, as the context is perceived as threatening.